2008
DOI: 10.1111/j.1467-971x.2008.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards non‐standard English in Singapore1

Abstract: This paper examines the problem of a curriculum which promotes a standard linguistic variety in a context where non-standardisms are common in the learners' milieu. There have been curricula which try to incorporate the non-standard and have its function discussed; some have considered the nonstandard a stepping-stone towards the standard; and yet others have tried to keep the non-standard out of the school context. We examine the Singaporean context with reference to English in the classroom, where the last o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 20 publications
0
34
1
Order By: Relevance
“…In the Philippines, while English is somewhat less pluristylistic (the local vernacular, Filipino, being more common in intimate contexts), a large percentage of the population nevertheless claims speaking or writing ability in English. Despite complaints about poor English standards (Thompson 2003), many Filipinosespecially of the younger generation -express positive attitudes towards PhilE and regard it as contributing to their sense of Filipino identity (Borlongan 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In the Philippines, while English is somewhat less pluristylistic (the local vernacular, Filipino, being more common in intimate contexts), a large percentage of the population nevertheless claims speaking or writing ability in English. Despite complaints about poor English standards (Thompson 2003), many Filipinosespecially of the younger generation -express positive attitudes towards PhilE and regard it as contributing to their sense of Filipino identity (Borlongan 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Being able to identify the guise as a friend or family member would, of course, eliminate any contextual ambiguity, locating the guise interaction squarely in the private domain. In their MG study with Singaporean junior high school participants, Tan and Tan (: 475), in contrast, led their participants to envision guise interactions taking place in the public domain through questionnaire items asking questions like: ‘Do you feel it is appropriate for a Maths teacher to speak like this person?’ For future MG studies investigating SCE/SSE attitudes among Singaporeans, researchers should take into account the ideal of rigid private/public domain boundaries being maintained, and design their studies accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Use of SCE with mathematics teachers, for example, was deemed far more acceptable than with English teachers. Observing that the participants ‘seem to want to carve out a space for Singlish in some finely calibrated contexts’, Tan and Tan (: 477) concluded that their responses ‘clearly indicate that there are occasions when some Singlish is appropriate, as well as occasions when it is not’.…”
Section: Previous Studies Of Singapore Englishmentioning
confidence: 99%
“…A case in point is Singapore, which Schneider (2007: 155−61) claims has entered phase four (endonormative stabilisation) of his Dynamic Model of the evolution of postcolonial Englishes, indicating (in Schneider's view), the broad acceptance and approval of the local form of English. Notwithstanding such progress, the emergence of a distinctive nativised variety has been deprecated by the island's establishment (Bokhorst‐Heng 2005; Wee 2005; Rubdy 2007; Tan and Tan 2008; Cavallaro and Ng 2009), who, in an effort to countervail the apparently deleterious influence of Colloquial Singapore English (or Singlish), initiated the Speak Good English Movement in 2000 to encourage Singaporeans to speak a more standard, internationally intelligible form of the language (Rubdy 2001).…”
Section: Introductionmentioning
confidence: 99%